Transcriptomes reflect the phenotypes of undifferentiated, granulocyte and macrophage forms of HL-60/S4 cells - Welch, David B. Mark; Jauch, Anna (Nucleus, 2017)
To understand the chromatin changes underlying differential gene expression during induced differentiation of human leukemic HL-60/S4 cells, we conducted RNA-Seq analysis on quadruplicate cultures of undifferentiated, granulocytic- and macrophage-differentiated cell forms. More than half of mapped genes exhibited altered transcript levels in the differentiated cell forms. In general, more genes showed increased mRNA levels in the granulocytic form and in the macrophage form, than showed decreased levels. The majority of Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways were significantly enriched in genes that exhibited differential transcript levels after either RA or TPA treatment. Changes in transcript levels for groups of genes with characteristic protein phenotypes, such as genes encoding cytoplasmic granular proteins, nuclear envelope and cytoskeletal proteins, cell adhesion proteins, and proteins involved in the cell cycle and apoptosis illustrate the profound differences among the various cell states. In addition to the transcriptome analyses, companion karyotyping by M-FISH of undifferentiated HL-60/S4 cells revealed a plethora of chromosome alterations, compared with normal human cells. The present mRNA profiling provides important information related to nuclear shape changes (e.g., granulocyte lobulation), deformability of the nuclear envelope and linkage between the nuclear envelope and cytoskeleton during induced myeloid chromatin differentiation.